ESTIMATION OF CADMIUM CONCENTRATION IN BLOOD AND URINE IN THE RESIDENTS ALONG RIVER YAMUNA REGION IN DELHI (Journal of Forensic Medicine & Toxicology, 2025)
Population neighbouring the Yamuna region in Delhi NCR are more vulnerable to health problems ongoing exposure to several potentially dangerous substances, such as heavy metals emitted during industrial production activities. While a large body of prior research has concentrated on occupational heavy metal exposure, there are comparatively few studies that examined ambient cadmium exposure in Delhi-NCR. This study aims to assess how much cadmium is exposed in the environment among Delhi-NCR individuals living close to the Yamuna area. A total of 144 participants, ranging in age from 16 to 45, were chosen among the population of our research locations, and all studies were conducted using written questionnaires. Samples of blood and urine are taken from every participant who provided consent for the collection of biological samples. All the subjects were included in the final analysis. The mean Cadmium concentration of blood was found 4.69±0.28 µg/dl. The maximum concentration of Cadmium was 14.76 µg/dl while minimum concentration was below the detection limit. The mean Cadmium concentration of the in urine was 0.03±0.002 mg/l. The residents of the above-selected area of Delhi-NCR had much higher blood and urine cadmium levels, according to this study.
Keywords: Cadmium levels; Blood cadmium; Urine cadmium; Yamuna toxicity